EVALUATION OF EFFICACY AND SAFETY OF ORAL VITAMIN D3 AND VITAMIN E AS AN ADD-ON-THERAPY TO METHOTREXATE IN PATIENTS OF MODERATE CHRONIC PLAQUE PSORIASIS - Narang, Garima; RANI, SEEMA; KATARIA, USHA; BHUTANI, GARIMA; SAINI, RAHUL (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study was conducted with the aim to evaluate the efficacy and safety of oral Vitamin D3 and Vitamin E as an add-on-therapy to methotrexate (MTX) in patients of moderate chronic plaque psoriasis. Methods: In this prospective, open-labeled, randomized, and comparative clinical study, a total of 120 patients of age 20–60 years with moderate chronic plaque psoriasis attending the dermatology outpatient department were randomly allocated into three groups of 40 each, i.e., Group M, Group D, and Group E. Group M received MTX (7.5 mg) tablet orally weekly, Group D received MTX (7.5 mg) and Vitamin D3 (60,000 IU) sachet orally weekly, and Group E received MTX (7.5 mg) weekly and Vitamin E (400 mg) daily. Efficacy assessment was done through the following primary parameters-psoriasis area and severity index (PASI) score, dermatology life quality index (DLQI), and psoriasis disability index (PDI), and secondary parameters such as Vitamin D deficiency and insufficiency among the study participants and improvement of serum 25(OH)D concentration. Adverse events were monitored. Results: PASI and DLQI were calculated at the time of recruitment (baseline), 1 month, 2 months, 3 months, and 4 months, and PDI and serum Vitamin D were calculated at baseline and 4 months. On intergroup comparison of PASI score and PDI, statistically significant results were seen at 4 months. DLQI showed significant results at 2, 3, and 4 months. Significant results were found in Group D which signifies improvement in serum Vitamin D levels. Mild side effects were seen at the end of 4 months. Conclusion: The present study suggested that Vitamin D as an add-on therapy was found to cause a significant reduction in psoriatic lesions. It could be a promising drug in patients with psoriasis to improve the psoriatic lesions, when combined can reduce the dose of MTX, thereby minimizing the side effects.